RARE EARTH ELEMENT DISTRIBUTION PATTERNS IN THE SOILS AROUND THE NIGERIAN RESEARCH REACTOR-1, (NIRR-1) IN ZARIA, NIGERIA - Garba, Ladan; B Ewa, I. O.; Oladipo, M. O. A.; Omeje, C. U. (European Scientific Journal, ESJ, 2012)
The Rare Earth Elements (REEs) are useful geochemical markers and retain group coherence in their geological environment. Here, the pattern of six REEs (La, Sm, Eu, Dy, Yb and Lu) determined by Instrumental Neutron Activation Analysis (INAA) of soils around the Nigeria Research Reactor-1 (NIRR-1), Zaria Nigeria is reported. REE distribution patterns for the soils covered in the investigation were identical, in other words exhibiting coherent fractionations from Low REE to High REE. The overall fractionation of the REEs for earth soil is depicted by the slope of the (REE)cn plot by the (La/Lu)cn in ratio. The REE plots obtained showed enrichment of (LREE)cn as against the (HREE)cn, which is the usual trend for all geological matrices. The REE chondrite-normalized plots showed both Europium and Dysprosium anomalies for the upper plain and flood plain sites with the latter exhibiting the characteristic features of fadama wet land.